Learning and playing in English language summer camps - Arany Sándor (2005)
English language teaching in the Hungarian school system gives students a wellworking simulated environment for acquiring the foreign language, but it lacks the excitement and pleasures of real-life communication. Indeed, for many students the greatest value in language learning is not gained through their classroom lessons, but through contact and interaction with foreigners. English language summer camps organized by native English speakers and Hungarian English teachers can provide the right place where students can crown al the efforts they have put in the learning of the language within the institutional system by using their knowledge for its real purpose: real-life communication. That is why in my thesis I look into the possibilities of language learning offered by a summer language camp, then I briefly overview the organisation process. The main focus is on the language learning activities that are carried out outside and inside the classroom as a characteristic of summer language camps. Finally, I draw my conclusion as to the usefulness of these camps by surveying evaluation forms filled in by ex-campers and teachers.